An application of the concept of a generalized central element - Al-Sharo, Kh.A.; Shemetkova, O. (Algebra and Discrete Mathematics, 2007)
With the help of the concept of a generalized central element we study finite groups with the given system of S-quasinormally embedded subgroups.